Local agriculture traditional knowledge to ensure food availability in a changing climate: revisiting water management practices in the Indo-Gangetic Plains. Issue 9 (20th October 2016) - Rivera-Ferre, M. G.; Di Masso, M.; Vara, I.; Cuellar, M.; Calle, A.; Mailhos, M.; López-i-Gelats, F.; Bhatta, G.; Gallar, D.
ABSTRACT: Climate variations are considered one of several interacting factors affecting food security. Specifically, in the Indo-Gangetic Plains, increased exposure to droughts and floods are expected. Local traditional knowledge in agriculture (LTKA) is proposed in this article as valid knowledge to ensure food availability under climate change, given its long experience in dealing with climate variability. Focused on water strategies, we have conducted a literature review on LTKA practices in the Indo-Gangetic Plains complemented with a questionnaire of experts to identify LTKA-based practices that might be useful in climate-change driven water scenarios. The practices identified are categorized as a) water harvesting and recycling; b) local irrigation systems; and c) and maintenance, conservation, and water allocation. We found that a) despite acknowledging the potential of LTKA to face floods and droughts, very few studies explicitly make the link between LTKA and climate change; and b) LTKA in water management heavily relays on social norms and local institutions and, thus, any attempts to replicate it need to consider this. We conclude that agroecology can help to promote these practices since it emphasizes the collective management from below as the main approach for the design of sustainable agroecosystems and, thus, include local institutions as an essential strategy for adaptation.